Challenges and prospects of COVID‐19 vaccine development based on the progress made in SARS and MERS vaccine development. Issue 3 (23rd September 2020) - Begum, Jubeda; Mir, Nasir Akbar; Dev, Kapil; Buyamayum, Bidyarani; Wani, Mohd Yaqoob; Raza, Meesam
Abstract: The outbreak of coronavirus disease 2019 (COVID‐19) as a pandemic has shaken the global health system and economy by their roots. This epidemic is still spreading and showing no signs of decreasing trend. Vaccination could be the only effective and economical means to control this pandemic. A number of research institutions and pharmaceutical companies have plunged into the race of vaccine development against COVID‐19 which are in various stages of development. An intriguing fact of coronavirus infections is that in every decade of the 21st century there is a new major coronavirus epidemic, namely, severe acute respiratory syndrome (SARS) in 2002, Middle East respiratory syndrome (MERS) in 2012, and now COVID‐19; and such epidemics are expected in future too. Since most of the biological characteristics of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) are still obscure, the scientists are relying on the information available on SARS‐CoV and to some extent on MERS‐CoV for designing and developing COVID‐19 vaccines. But there is a need of vigorous testing for immunogenicity, safety, efficacy, and level of protection conferred in the hosts. This review focuses on the challenges and prospects of vaccine development against COVID‐19. It highlights seriousness, bottlenecks in vaccine development, possible vaccine candidates, different vaccine strategies, safety evaluation issues, and vaccine production processes pertaining to COVID‐19 based on the knowledge acquired on SARS and MERS vaccine development in the past.